The torture victim and the dentist: The social and material dynamics of trauma re-experiencing triggered by dental visits - Høyvik, Ann Catrin; Willumsen, Tiril; Lie, Birgit; Hilden, Per Kristian (Torture Journal, 2021)
Introduction: The flow of refugees towards Europe over the past decade has placed increased demands on the health care services. A significant proportion of refugees have been subjected to torture involving their mouth or teeth, still the importance of oral health challenges is often overlooked or underestimated in the rehabilitation of torture victims. In this qualitative study, we set out to explore the processes that complicate torture victims’ ability to engage in and tolerate dental procedures. Methods: Ten resettled refugees with experience of torture were recruited among patients affiliated with specialized clinics for oral health rehabilitation in Norway. Data were collected through semi-structured exploratory interviews, and analyzed using a qualitative content analysis approach. Results and discussion: We present an exploration of what we have called the social and material anatomy of the triggering event; the process through which trauma-related reactions are produced in torture victims in the course of undergoing dental treatment. All professionals who work with torture survivors should be aware that these individuals often suffer from oral health problems that may affect both their physical and their psychological quality of life. However, although dental treatment is essential, it may still represent a major challenge. Our data suggest, we propose, that dental treatment often involves an experience being suspended, albeit temporarily, in an objectified position, acted on by subjects capable of producing deeply undesirable mental, emotional or bodily states. Three main categories emerged as the most prominent factors with such an agentic capacity: 1) pain, 2) traumatic memories and 3) the dentist. Submitting to dental treatment hence requires the patient’s willingness to give in to the actions of these factors, and avoiding treatment may therefore, in this situation, represent a means of retaining control.